Numerical simulation of two-phase flow around flatwater competition kayak design-evolution models - Mantha, V. R.; Silva, A. J.; Marinho, D. A.; Rouboa, A. I. (Journal of Applied Biomechanics, 2013)
The aim of the current study was to analyze the hydrodynamics of three kayaks: 97-kg-class, single-rower, flatwater sports competition, full-scale design evolution models (Nelo K1 Vanquish LI, LII, and LIII) of M.A.R. Kayaks Lda., Portugal, which are among the fastest frontline kayaks. The effect of kayak design transformation on kayak hydrodynamics performance was studied by the application of computational fluid dynamics (CFD). The steady-state CFD simulations where performed by application of the k-omega turbulent model and the volume-of-fluid method to obtain two-phase flow around the kayaks. The numerical result of viscous, pressure drag, and coefficients along with wave drag at individual average race velocities was obtained. At an average velocity of 4.5 m/s, the reduction in drag was 29.4% for the design change from LI to LII and 15.4% for the change from LII to LIII, thus demonstrating and reaffirming a progressive evolution in design. In addition, the knowledge of drag hydrodynamics presented in the current study facilitates the estimation of the paddling effort required from the athlete during progression at different race velocities. This study finds an application during selection and training, where a coach can select the kayak with better hydrodynamics.